Separation Techniques for Quantification of Radionuclides in Environmental Samples - Dusan Galanda; Pavol Rajec; Lubomir Mátel; Olga Rosskopfová; Silvia Dulanská (The Scientific World Journal)
The reliable and quantitative measurement of radionuclides is important in order to determine environmental quality and radiation safety, and to monitor regulatory compliance. We examined soil samples from Podunajske Biskupice, near the city of Bratislava in the Slovak Republic, for the presence of several natural (238U, 232Th, 40K) and anthropogenic (137Cs, 90Sr, 239Pu, 240Pu, 241Am) radionuclides. The area is adjacent to a refinery and hazardous waste processing center, as well as the municipal incinerator plant, and so might possess an unusually high level of ecotoxic metals. We found that the levels of both naturally occurring and anthropogenic radionuclides fell within the expected ranges, indicating that these facilities pose no radiological threat to the local environment. During the course of our analysis, we modified existing techniques in order to allow us to handle the unusually large and complex samples that were needed to determine the levels of 239Pu, 240Pu, and 241Am activity. We also rated three commercial techniques for the separation of 90Sr from aqueous solutions and found that two of them, AnaLig Sr-01 and Empore Extraction Disks, were suitable for the quantitative and reliable separation of 90Sr, while the third, Sr-Spec Resin, was less so. The main criterion in evaluating these methods was the chemical recovery of 90Sr, which was less than we had expected. We also considered speed of separation and additional steps needed to prepare the sample for separation.